The impact of medication belief on adherence to infliximab in patients with Crohn’s disease - Li, Shuyan; Ma, Yan; Sun, Hongling; Ni, Zijun; Hu, Shurong; Chen, Yan; Lan, Meijuan (Frontiers in Pharmacology, 2023)
Objective: Crohn's disease (CD) is an incurable chronic disease that requires long-term treatment.As an anti-tumor necrosis factor (TNF) agent, Infliximab (IFX) is widely used in the treatment of Crohn's disease, while the adherence is not high. The purpose of this study was to investigate the adherence to IFX among CD patients in China and evaluate the association between medication belief and IFX adherence. Methods: Demographic data, clinical information and patients' medication beliefs were collected using an online questionnaire and reviewing electronic medical records (EMRs). The Beliefs about Medicines Questionnaire (BMQ)-specific was used to assess medication beliefs which contains the BMQ-specific concern score and the BMQ-specific necessity score. An evaluation of adherence factors was conducted using univariate and multidimensional logistic regression analyses. Results: In all, 166 CD patients responded the online questionnaire among which 77 (46.39%) patients had high adherence. The BMQ-specific concern score in patients in low adherence was 30.00 and in high adherence patients was 27.50, and patients with lower BMQ-specific concern score had higher adherence(P=0.013). The multiple regression analysis showed that the BMQ-specific concern score (OR=0.940,95%CI:0.888 0.996) significantly affected the IFX adherence in CD patients. Otherwise, gender, marital status, time spent on the way (including the waiting time in infusion center) and accommodation to the center were also the influencing factors of adherence. Conclusion: The IFX adherence to CD in China was not high. Medicine concerns may be predictive factor of adherence. Education, the duration of IFX therapy and experience of adverse effects were not significantly associated with IFX adherence. By enhancing knowledge and relieving medicine concerns, we may increase patients’ adherence to IFX.